A campus start-up ecosystem for mechanical engineering students: Challenges, approaches, catalysts and solutions. Issue 1 (February 2022) - Pradeep, M.; Satish, K.P.
Start-up ecosystems are emerging rapidly worldwide. The speed of technology innovation and the diversity of business ideas keep the start-up landscape in constant flux. While many emerging start-ups are in the areas of electronics and information sciences, the field of mechanical engineering has huge potential that has yet to be exploited. Today's mechanical engineering students need to be well positioned to recognize and seize potential start-up opportunities. This study examines the involvement of Indian mechanical engineering students in campus start-ups and the challenges they face in nascent entrepreneurship. Structural equation modelling was applied to a sample of 396 final-year undergraduate mechanical engineering students from the APJ Abdul Kalam Technological University in Kerala. Data collection was achieved through a questionnaire developed on the basis of existing literature, feedback and market research. The findings highlight the currently prevailing barriers and best practices, and recommendations are derived for leveraging the nascent entrepreneurship potential of the mechanical engineering discipline. The negative effects of the barriers are positively moderated by the activities of campus-based entrepreneurship centres. The study results provide insights into the role of universities, higher education departments and government agencies in promoting a sustainable campus start-up culture through entrepreneurial learning.